HABITS OF USING INTERNET AND DIGITAL DEVICES IN EDUCATION - Mackare, Kristīne; Jansone, Anita (SOCIETY. INTEGRATION. EDUCATION. Proceedings of the International Scientific Conference, 2018)
According to Central Statistical Bureau data of 2017 at least 46.8% of Latvian population are involved in educational activities. Such digital devices as computers (both desktop computers and laptop computers), tablets, smartphones, book readers, etc. and the internet directly or indirectly are used in both formal and non-formal education. Digital devices can be used in training or study process, or some part of it directly, as well as students or training participants may be assigned tasks to be performed with these devices – searching for information, reading and learning e-material, writing articles, etc. In addition to statistical data research, two e-polls were conducted for respondents who are computer users in different age groups. Respondents were asked about their habits in using the internet and digital devices, additional interest was about which of the digital tools are used and for what purposes these devices are used. All answers have been analysed. The survey results show that the responses provided by the participants of the sample group are very close to the whole population, both for the use of the Internet and digital devices. The results also show the purpose of using digital devices, especially in education, and which devices are most commonly used for each purpose. More than 90% of respondents use digital devices to get information. In order to participate successfully in e-learning and e-studies, users need both good e-skills and well-designed e-learning materials: high-quality content, comfortable, easy-to-understand and comprehensible text, suitable formatting parameters of text.